Accountability and Transparency in Public Sector Accounting: A Systematic Review - Ratna Sari; Muslim Muslim (Pascasarjana STIE Amkop Makassar, 2023)
This study aims to systematically review the mechanisms that promote accountability and transparency in public sector accounting, focusing on regulatory frameworks, auditing practices, digital transformation, stakeholder engagement, and ethical considerations. The study employs a systematic review design, following PRISMA guidelines to ensure a rigorous and transparent approach. The literature search spans from 2000 to 2023, including peer-reviewed journal articles, books, and official reports. Keywords such as